M-health system backend supported by an actors model (2015)
Given the serious impact that cardiovascular diseases are having in Colombia's deaths, the Colombian School of Engineering has been developing a platform for remote, real time, cardiac signals processing. One of the main challenges of this type of platform, assuming a relatively large population continuously transmitting their signals, is to guarantee good response times for all system's stakeholders (doctors, family, etc.), which is not always possible with the application models that have been traditionally used to build most of services that reside on the Web. This article describes an alternative software architecture proposed for the backend of such telemedicine system, which considers the non-blocking and actor-based programming models, as an alternative to the multi-thread model, and as a mean to simplify such system's scalability.